Single and combined effects of Di-2-ethylhexyl phthalate and bisphenol A on life traits of the tropical micro-crustacean Ceriodaphnia cornuta - Van-Tai Nguyen; Manh-Ha Bui; Emilie Strady; Thuy-Chung Kieu-Le; Ba-Trung Bui; Thanh-Son Dao (Vietnam Journal of Science, Technology and Engineering, 2020)
Plastics, plastic additives, and their emission have attracted significant attention and concern both socially and scientifically. Di-2-ethylhexyl phthalate (DEHP) and bisphenol A (BPA) are two of the many plastic additives widely found in aquatic environments, which can have severe impacts on aquatic animals like micro-crustaceans. Therefore, this study assessed the chronic effects of DEHP and BPA, both individually and jointly, at environmental concentrations (e.g. 50 and 500 µg/l) on the survival rate, reproduction, and growth of the tropical micro-crustacean Ceriodaphnia cornuta. We found that each of the two plastic additives, and a mixture of the two, had some influence on the survivorship of C. cornuta. While DEHP marginally enhanced the reproduction of the animals, BPA strongly inhibited it. Additionally, the mixture of DEHP and BPA caused a synergistic effect on reproduction but an antagonistic effect on the growth of C. cornuta. Both DEHP and BPA induced a significantly longer body of C. cornuta when exposed to these plastic additives. Our results showed that the tropical microcrustacean C. cornuta is more sensitive to DEHP and BPA than the temperate micro-crustacean D. magna in relation to body length development and reproductive characteristics. Our findings enrich the knowledge of DEHP and BPA toxicity to tropical micro-crustaceans. Besides, our results are also of significant value to freshwater monitoring and environmental risk assessments of plastic additives.